WHEN DOES SURVEILLANCE ART CROSS THE LINE? - Pollack, Barbara (ARTnews, 2014)
Over the past few years, a number of photography exhibitions seem to have anticipated the case of Foster v. Svenson in their examinations of voyeurism, surveillance, and privacy issues. As early as 2003, the International Center of Photography presented "Strangers: The First ICP Triennial of Photography and Video," a survey that included many examples of photographic invasions, and in 2010 the San Francisco Museum of Modern Art presented "Exposed: Voyeurism, Surveillance, and the Camera Since 1870." Now, the Transformer Station in Cleveland is showing "Unknown: Pictures of Strangers," the New York Public Library is planning an exhibition scheduled for Nov 2014 titled "Public Eye: 175 Years of Sharing Photography (1839-2014)," and the Scottsdale Museum of Contemporary Art is planning "Covert Operations: Investigating the Known Unknowns," scheduled to open in 2015. Here, Pollack what it means to invade others' privacy in the name of art.